Hubungan Antara Kuantitas dan Kualitas Tidur Dengan Uji Kompetensi DIII Keperawatan Poltekkes Kemenkes Jakarta I - Amelia Arnis (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
Abstract A person's sleep quality is said to be good if it does not show a variety of signs of sleep deprivation and does not experience sleep problems. Sleep disorders are commonly found among young adults, especially students who later can lead to reduced concentration of learning and health problems. This can cause the achievement of academic achievement optimally because the learning process is disrupted. The purpose of this study was to determine the relationship of quantity and quality of sleep with the competency test DIII Nursing Ministry of Health Polytechnic Jakarta I. The research design used was an analytical method with a cross sectional design. The research sample was a total sampling of students DIII Health Ministry Polytechnic nursing Jakarta I who had graduated in 2017 with 76 respondents. Sleep quality data was taken using the Pittsburg sleep quality index (PSQI) and the 2017 competency test graduation value. The results of this study indicate there is no relationship between the quality and quantity of sleep and the graduation of nursing competency tests.